Towards evidence-based approaches to monitoring and evaluating age-friendly cities and communities: Reflections from the Western Pacific and Nordic Regions - Xu, Wenqian ; 0000-0003-4274-5468; Maija Zechner, Minna; Viknaraj Sivabalan, Thava; Low, Lian Leng; Shon, Changwoo; Chen, Honglin; Reuter, Arlind ; 0000-0002-8407-7958; Turner, Diane; Tiilikainen, Elisa; Kiyota, Emi; Iwarsson, Susanne (Creating age-friendly environments: research, policy and practice, Shanghai, China, 2024-01-01 - 2024-06-30, 2025)
Age-Friendly Cities and Communities (AFCC) is a key global WHO initiative aimed at fostering environments that promote healthy aging for everyone. As AFCC initiatives continue to expand, there is an increasing need to enhance monitoring and evaluation systems to effectively assess their progress and impact. However, significant knowledge gaps persist, particularly in the development of evaluation methods and AFCC indicators. Drawing on discussions and outcomes from an international, interdisciplinary expert meeting on age-friendly environments held in Shanghai in May 2024, this article offers a synthesis of key insights and reflections. We present examples from AFCCs in the Western Pacific and Nordic regions, and recommendations to enhance monitoring and evaluation with a focus on indicators. This includes defining clear objectives, addressing the diverse needs of target groups, tailoring evaluation methods, assessing both the processes and outcomes of AFCC initiatives. Regarding AFCC indicators, we argue that several areas require further attention, including the need for a robust framework that emphasizes equity and inclusivity and the varied experiences of older adults. For example, this framework should guide the development of indicators that address older adults’ needs during life transitions, reflect societal transitions, and leverage interconnected age-friendly domains to promote health and well-being. We recommend developing AFCC indicators through participatory and developmental processes that encourage stakeholder engagement, particularly involving older adults. Research is needed to develop context-specific indicators and evaluation tools through local and regional studies, validate the indicators across diverse contexts, and incorporate global best practices for using indicators to achieve policy impact.